Who agrees more? The role of age, education, and the ability to solve verbal analogies in acquiescence - Patrik Havan; Peter Halama; Vladimíra Čavojová; Michal Kohút (Current Issues in Personality Psychology)
Background Acquiescence as one of the response styles is the participant’s tendency to shift answers to agreement rather than to disa-greement regardless of the items’ content. Acquiescence together with other response styles could be a serious threat to the results of research. It can be affected by several individual characteristics including cognitive abilities. We explored the rela-tionship between the ability to solve verbal analogies, age, education, and acquiescence.